Dynamic Plasmonic Platform To Investigate the Correlation between Far-Field Optical Response and SERS Signal of Analytes - Nguyen, Mai; Kherbouche, Issam; Braik, Macilia; Belkhir, Abderrahmane; Boubekeur-Lecaque, Leïla; Aubard, Jean; Mangeney, Claire; Felidj, Nordin (ACS omega, 2019)
The design of surface-enhanced Raman spectroscopy (SERS) platforms based on the coupling between plasmonic nanostructures and stimuli-responsive polymers has attracted considerable interest over the past decades for the detection of a wide range of analytes, including pollutants and biological molecules. However, the SERS intensity of analytes trapped inside smart hybrid nanoplatforms is subject to important fluctuations because of the spatial and spectral variation of the plasmonic near-field enhancement (i.e., its dependence with the distance to the nanoparticle surface and with the localized surface plasmon resonance). Such fluctuations may impair interpretation and quantification in sensing devices. In this paper, we investigate the influence of the plasmonic near-field profile upon the Raman signal intensity of analytes trapped inside thermoresponsive polymer-coated gold nanoarrays. For this, well-defined plasmonic arrays (nanosquares and nanocylinders) were modified by poly(N-isopropylacrylamide) (PNIPAM) brushes using surface-initiated atom-transfer radical polymerization. Molecular probes were trapped inside these Au@PNIPAM nanostructures by simple physisorption or by covalent grafting at the end of PNIPAM brushes, using click chemistry. The SERS spectra of molecular probes were studied along various heating/cooling cycles, demonstrating a strong correlation between SERS intensities and near-field spectral profile of underlying nanoparticles, as confirmed by simulations based on the finite difference time domain method. Thermoresponsive plasmonic devices thus provide an ideal dynamic SERS platform to investigate the influence of the near-field plasmonic profile upon the SERS response of analytes.